Self esteem dan Risk Taking Behavior dengan Perilaku Narsistik Remaja Penggunan Media Sosial - Dimas Agil Permadi; M. Nizar Dairobi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2021)
The purpose of this study was to determine the relationship between self-esteem and risk taking with adolescent narcissistic behavior using social media. This study uses self-esteem variables (X1) and risk taking behavior (X2), as well as narcissism as the dependent variable (Y). This study uses Google Forms in data collection and uses a quota sampling technique, meaning that the number of samples used has been determined. In this study, a sample of 150 teenagers aged 12-24 years old and active users of social media for 2 years was used. Based on regression analysis, it shows that self-esteem and risk-taking behavior simultaneously have a relationship with the narcissistic behavior of adolescent social media users with a p value = 0.000 and an effectiveness contribution of 14.1%. Partially, self-esteem has a significant relationship with the narcissistic behavior of adolescent social media users with p value = 0.001 in a negative direction, in contrast to risk taking behavior which has no partial relationship with the narcissistic behavior of adolescent social media users.